In vivo proton MR spectroscopy of gliomatosis cerebri: Diagnosis and exploration of tumor metabolism. (September 2016) - Gotsis, E.D.; Gkotsi, D.S.; Pissakas, G.; Seimenis, I.
Abstract : Introduction: Gliomatosis cerebri was not recognised as a separate entity till a few years ago and it was thought to be a rare entity. Advanced imaging methods and In Vivo Proton MR spectroscopy (MRS) have contributed to the safe diagnosis of the disease, which is not such a rare entity as once thought. Purpose: To explore the capabilities of In Vivo Proton MR Spectroscopy not only for diagnosing the disease but also for exploring the metabolism of the tumor cells. Materials and methods: In an extended period of 16 years, 147 patients were diagnosed with gliomatosis cerebri by In Vivo MR Spectroscopy (single voxel at selected areas and 3D Spectroscopic Imaging). Metabolic maps of choline and creatines showed tumor infiltration. For some patients serial MRS was also performed. Results: In virtually all cases except one – a patient diagnosed with gliomatosis cerebri for whom the biopsy showed limbic encephalitis – biopsy confirmed a "glioma" or in cases without biopsy the progress of the disease confirmed the MRS diagnosis. What was a surprise was that in most cases creatine concentration was higher than normal leading to the notion that part of the tumor cells maintain for some time normal cell metabolism (aerobic glycolysis). With advance of time, the metabolism switches to the primitive tumor cell metabolism. Conclusion: In Vivo Proton MR Spectroscopy is a potent probe for the diagnosis of gliomatosis cerebri as well as for exploring tumor cell metabolism. Disclosure: None of the authors has anything to declare.